Analisis Daya Tarik Wisata pada Museum Gedung Sate - Hidayat, Taufiq; Rahmadilla, Rahmadilla; Ratuku, Gesiva Arila; Adiscallysta, Mutiara Kartika (Sekolah Tinggi Ilmu Ekonomi Pariwisata Yapari (STIEPAR YAPARI) Bandung, 2024)
Tourist attractions are anything that encourages someone to visit a particular location. There are two main categories of tourist attractions: natural attractions and man-made attractions. Currently, many people are visiting many beautiful places in Indonesia, especially the city of Bandung. The city of Bandung has many diverse tourist attractions, ranging from natural tourism, artificial tourism, culinary tourism, to historical tourism. However, with the variety of tourist attractions in the city, do museums still remain a choice for tourists? The focus of this research is to see what attracts tourists to the Gedung Sate Museum in Bandung. One of the main educational and cultural tourist attractions in West Java is Gedung Sate, which is considered an icon of colonial architecture and history. This study will identify the main components that make a museum interesting, such as architectural value, historical elements, and visitor experience. This will be done through a qualitative approach. Data will be collected through interviews with managers and visitors, as well as the examination of relevant documents. The results of this research are expected to help develop more efficient promotional strategies to enhance the tourist attraction of the Gedung Sate Museum and significantly contribute to the growth of the local tourism sector.